Energy and environmental sustainability of Jatropha‐Biofuels Chain from nontoxic accessions in Cameroon. Issue 1 (4th May 2018) - Vrech, Alessandro; Ferfuia, Claudio; Bessong Ojong, Willington; Piasentier, Edi; Baldini, Mario
Abstract : A Jatropha‐biofuel chain was organized in the north‐west of Cameroon. The aim of the project was to implement an integrated biofuel chain, based on nontoxic Jatropha cultivation, which could provide vegetable oil for energy use instead of fossil fuel and, contemporary supply cake protein for the rural population. The main objective of this study was to quantify the cumulative energy demand (CED) and global warming potential (GHG) in obtaining Jatropha vegetable oil (JVO) as biofuel in comparison with conventional diesel fuel adopting the Life Cycle Analysis method (ISO 14040, ISO 14044). Adopting both Well‐to‐Wheel or Well‐to‐Tank value of diesel fossil fuel as reference, a significant reduction in energy required and greenhouse gas emissions would be obtained by JVO utilization with respect to the fossil fuel. The utilization of a nontoxic Jatropha curcas accession is very positive, as it ensures greater protection of human health with respect to the toxic accessions. © 2018 American Institute of Chemical Engineers Environ Prog, 38: 305–314, 2019